2014
DOI: 10.1128/iai.01840-14
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of the Capsule and Impact of Serotype 4 Switching on Streptococcus mitis

Abstract: eThe polysaccharide capsule surrounding Streptococcus pneumoniae is essential for virulence. Recently, Streptococcus mitis, a human commensal and a close relative of S. pneumoniae, was also shown to have a capsule. In this study, the S. mitis type strain switched capsule by acquisition of the serotype 4 capsule locus of S. pneumoniae TIGR4, following induction of competence for natural transformation. Comparison of the wild type with the capsule-switching mutant and with a capsule deletion mutant showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Different polysaccharides have been described for selected strains of S. oralis and S. mitis (16, 17), but their structural variation within the species has not been examined systematically (33). Interestingly, serological cross-reactions between pneumococci and other streptococci of uncertain identity were observed in the past (34–37).…”
Section: Introductionmentioning
confidence: 99%
“…Different polysaccharides have been described for selected strains of S. oralis and S. mitis (16, 17), but their structural variation within the species has not been examined systematically (33). Interestingly, serological cross-reactions between pneumococci and other streptococci of uncertain identity were observed in the past (34–37).…”
Section: Introductionmentioning
confidence: 99%
“…TEM demonstrated that, compared to the wild type S. mitis strain (Fig. 1c), which we have previously shown expresses a capsule with no known S. pneumoniae serotype homologue (Rukke et al, 2014), the S. mitis TIGR4 cps strain had a more obvious and relatively thick capsule layer (Fig. 1b) similar to the capsule layer seen with S. pneumoniae TIGR4 (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…We have previously shown expression of the TIGR4 S. pneumoniae serotype 4 capsule fails to make the S. mitis SK142 strain virulent in mice (Rukke et al, 2014). To assess whether there were major morphological changes in the capsule expressed by S. pneumoniae TIGR4 and S. mitis TIGR4 cps strains, we utilised a TEM method that preserves the capsular polysaccharide to visualise and measure the depth of the capsule, whilst also observing the density and arrangement of the surface sugars.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus mitis is one of the earliest commensal colonizers of the human oral cavity and resides in the oral mucosa from early infancy and throughout life. In immunocompetent persons, S. mitis is rarely associated with disease as it survives poorly in blood and is immediately cleared . In immunocompromised patients, however, it is the oral commensal streptococcal species that is most frequently associated with endocarditis or septicemia .…”
Section: Introductionmentioning
confidence: 99%